Keragaman Genetik 19 Genotipe Cabai Rawit Merah (Capsicum frutescens) serta Ketahanannya terhadap Kutu Daun (Aphis gossypii) - Riti, Estriana; Syukur, Muhamad; Maharijaya, Awang; Hidayat, dan Purnama (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
The information on birds eye chili (Capsicum frutescens L.) resistance to melon aphids (Aphis gossypii) is rarely reported. Objectives of this research were to evaluate genetic variability of 19 genotypes bird chili and identify the potential genotypes resistant to A. gossypii. This research consisted of two experiments. The first experiment was conducted in April-December 2015 at Leuwikopo Experimental Field, Faculty of Agriculture IPB. Genetic materials used were 19 genotypes of bird chili from Plant Breeding Laboratory IPB which were planted from seedling stage until harvesting stage. The second experiment was conducted in May 2017-May 2018 at Faculty of Agriculture, IPB Darmaga Campus. Material used were 19 genotypes of bird chili at seedling stage, and melon aphids which were collected from Leuwikopo Experimental Field IPB. Melon aphid infestation method used no-choice test. The results showed the genetic variability of bird chili had more than 0.30 coefficient of dissimilarity. Genetic variability for canopy width, anther length, fruit weight, and fruit length were classified to broad, but total fruit weight per plant was classified to narrow. There were six genotypes clasified resistant to melon aphid, i.e., C332, C343, C333, C334, C290, C346. The potential genotypes for breeding program of bird chili resistant to melon aphid were C343 and C334.Keywords: Aphis gossypii, Capsicum frutescens, cluster, resistant variety